PENGARUH FAKTOR DISTRESS RISK DALAM MENJELASKAN EFEK ANOMALI MOMENTUM - Bertha Silvia Sutejo (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2007)
The objective of this research was to study the effect of momentum anomaly and distress risk. This research also examines the different market effects on potential relationship between momentum and distress risk and prepare indirect empirical evidence on EMH in Indonesia. Sample of this research was based on manufacturing companies listed in Jakarta Stock Exchange from July 1992 – June 2003. The statistical method used to test the hypothesis was regression analysis. The study results were as follows: first, the result provides no support for the hypothesis that the distress risk can explain momentum effect in stock return; second, the result also provides no support for the hypothesis that there is no different influence on potential relationship between momentum and distress risk at bullish market or bearish market. This study found that distress risk and momentum make the size and B/M have a positive relationship with stock return on bullish market. But distress risk and momentum make size and B/M have a negative relationship with stock return on bearish market.